Effect of 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitor on Disease Activity in Patients With Rheumatoid Arthritis: A Meta-Analysis. Issue 8 (February 2015) - Xing, Bin; Yin, Yu-Feng; Zhao, Li-Dan; Wang, Li; Zheng, Wen-Jie; Chen, Hua; Wu, Qing-Jun; Tang, Fu-Lin; Zhang, Feng-Chun; Shan, Guangliang; Zhang, Xuan
Abstract : Abstract: HMG-CoA reductase inhibitors (also known as statins) are widely used as lipid-lowering agents in patients with rheumatoid arthritis (RA) to reduce their cardiovascular risk. However, whether they have an effect on RA disease activity is controversial. This study aimed to investigate the effect of statins on disease activity in RA patients. A systematic literature review was performed using the MEDLINE, EMBASE, Cochrane Library, ISI WEB of Knowledge, Scopus, and Clinical Trials Register databases. Only prospective randomized controlled trials or controlled clinical trials comparing the efficacy of statins with placebo on adult RA patients were included. The efficacy was measured according to the ACR criteria, EULAR criteria, DAS28, HAQ score, ESR, or CRP. The Jadad score was used for quality assessment. The inverse variance method was used to analyze continuous outcomes. A fixed-effects model was used when there was no significant heterogeneity; otherwise, a random-effects model was used. For stability of results, we performed leave-one-study-out sensitivity analysis by omitting individual studies one at a time from the meta-analysis. Publication bias was assessed using Egger test. A total 13 studies involving 737 patients were included in the meta-analysis; 11 studies were included in the meta-analysis based on DAS28, while the other 2 studies were only included in the meta-analysis based on ESR or CRP. The standardized mean difference (SMD) in DAS28 between the statin group and the placebo group was −0.55 (95% CI [−0.83, −0.26], P  = 0.0002), with an I 2 value of 68%. Subgroup analysis showed that patients with more active disease tended to benefit more from statin therapy (SMD −0.73, P  = 0.01) than patients with moderate or low disease activity (SMD −0.38, P  = 0.03). Statin therapy also significantly reduced tender joint counts, swollen joint counts, ESR, and CRP compared with placebo, but the reduction in HAQ score and VAS was not significant ( P  > 0.05). This meta-analysis suggested that statin therapy might be effective in the reduction of RA disease activity measured by DAS28, TJC, SJC, as well as ESR and CRP.